Pengaruh Refleksi Telapak Kaki Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di Rumah Sakit Kota Tangerang - Ningsih, Sonia Sulistia; Wahyu, Afnijar (Universitas Murni Teguh, 2024)
Hypertension is a condition in which there is an increase in blood pressure above normal, namely systolic 140 mmHg indicates the phase of blood being pumped by the heart and the diastolic phase 90 mmHg indicates the phase of blood returning to the heart. Hypertension is a medical condition with a high prevalence. The purpose of this study was to determine the Effect of Foot Reflexology on Reducing Blood Pressure in Hypertensive Patients. This study used a quasi-experimental without a control group with a sample size of 29 people and a total sampling technique. The bivariate test is a paired t-test. The results of the studyusing the paired t-test showed that the average blood pressure with a difference in pretest and posttest values was p-value = 0.000 (systolic), p-value = 0.000 (diastolic) where the significance value was p <0.05. It can be concluded that there is a significant effect of foot reflexology massage treatment on blood pressure. Physiologically, providing foot reflexology massage therapy can increase blood flow.